2003
DOI: 10.1016/s1078-5884(03)00380-0
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Outcome in Ruptured Abdominal Aortic Aneurysm: A Prospective Study of 100 Consecutive Cases

Abstract: The scoring system accurately predicted operative mortality. The score was available in the majority of cases and may help the surgeon give informed consent to patients and relatives prior to surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 15 publications
1
30
1
Order By: Relevance
“…2,6,[8][9][10][11][12][13]16,17 These figures confirm the significant predictive effect of the index but also its failure to consistently identify a subgroup of patients with 100% mortality in which surgery should be withheld. The authors of the meta-analysis speculated that the utility of the index seemed to be impeded by variability in scoring resulting from missing or nondiagnostic data, particularly with regards to ECG.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…2,6,[8][9][10][11][12][13]16,17 These figures confirm the significant predictive effect of the index but also its failure to consistently identify a subgroup of patients with 100% mortality in which surgery should be withheld. The authors of the meta-analysis speculated that the utility of the index seemed to be impeded by variability in scoring resulting from missing or nondiagnostic data, particularly with regards to ECG.…”
Section: Discussionmentioning
confidence: 80%
“…2,[8][9][10] Subsequent studies, however, yielded inconsistent results. 6,[11][12][13][14][15][16][17] Some found the index to be a poor predictor and failed to show a statistical association with death, 12-14 whereas others found a strong correlation.…”
Section: Discussionmentioning
confidence: 99%
“…17 Ten series have examined the validity of the Hardman Index; only one has been prospective. 3,8,9,13,16,[18][19][20][21][22] Initial reports and consensus was that the Hardman Index accurately predicted death after ruptured AAA. The presence of three or more variables was widely held to be fatal 8,9 ; however, more recent data have shown that the instrument 73 107 0 41 70 1 2 Cardiac dysfunction, suprarenal AAA 79 96 1 38 67 1 3 Cardiac dysfunction, chronic renal failure 83 121 3 88 91 2 4 Cardiac dysfunction 87 111 4 88 91 3 5 Cardiac dysfunction, chronic renal failure 89 120 3 57 77 2 6 Severe COPD 80 97 1 31 63 1 7 Previous disabling stroke 71 120 2 79 87 2 8 Pre-existing severe brain injury 76 100 1 31 63 2 9…”
Section: Discussionmentioning
confidence: 99%
“…22 Indeed, in the only other reported prospective study, data were missing on almost a third of patients. 9 The POSSUM score is a tool that was designed to support comparative audit. It is important to recognize that it has never been recommended for outcome prediction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation